Project-Based Learning in Indonesian Junior High School Science Education for SDG 4: Teachers’ Perceptions, Practices, and Implementation Challenges - Martini Martini; Erman Erman; I Gusti Made Sanjaya (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To explore Indonesian junior high school science teachers’ perceptions, practices, and challenges in implementing Project-Based Learning (PjBL) in science education, particularly in relation to the promotion of quality education as reflected in SDG 4. The study also examined the relationship between teaching experience, regional background, teachers’ perceptions, and the frequency of PjBL implementation. Method: A survey was conducted involving science teachers from various regions of Indonesia with different teaching experiences. Data were collected using a questionnaire developed based on core PjBL indicators, including project planning, implementation, assessment, and reflection. The data were analyzed using descriptive analysis, chi-square tests, and binomial tests. Results: The findings showed that most science teachers had positive perceptions of PjBL and recognized its potential to enhance student engagement, collaboration, problem-solving, creativity, and critical thinking skills. However, positive perceptions did not automatically lead to frequent classroom implementation. Several challenges were identified, including limited time, varying student readiness, inadequate facilities, difficulties in project assessment, and limited understanding of inquiry-oriented and reflective PjBL practices. Novelty: The study highlights the gap between teachers’ positive perceptions and actual PjBL implementation in Indonesian junior high school science education. It contributes to SDG 4 by emphasizing the need for sustained professional development to strengthen teachers’ pedagogical competence and support more inclusive, meaningful, and quality science learning.